Relative reinforcement from physical activity in real-world environments: a novel application of behavioral economics. - Foxx, Ricarda K.; Jake-Schoffman, Danielle E.; Mathews, Anne E.; Cheong, JeeWon; Yurasek, Ali M. (Journal of Behavioral Medicine, 2022)
Behavioral economics suggests that individuals are likely to engage in a behavior if it is more reinforcing and readily available than other possible options. In real-world environments, sedentary behaviors are often more reinforcing and easily available than physical activities. In order to promote regular physical activity in an environment with sedentary alternatives, it is important to understand the proportion of overall reinforcement that is derived from physical activity (i.e., relative reinforcement, RR). Conceptually similar laboratory-research supports this notion, but applications to individual, real-world environments remain understudied. The current study used a novel survey-based approach to estimate the RR of common physical activities. Healthy adults (N = 348, M age = 39.0 ± 8.7) from the United States completed an online survey between April–May 2020, including a modified activity survey with ten physically active and ten sedentary activities. Regression analysis showed that total RR of physical activity was related to greater physical activity levels when controlling for enjoyment and other covariates. Four factors were identified (household, conditioning, sports, and outdoor activities) using exploratory structural equation modeling, but internal consistency was limited when items were constrained to each factor in the structural equation model. Previous laboratory findings on overall RR of physical activity were replicated with the survey-based measure, but further improvement for relative reinforcement of different sub-domains of physical activity is needed. Researchers and practitioners can use this survey to determine attractive physical activities on the individual level that can compete with sedentary leisure activities.